Immunosuppressive Protein Signatures Carried by Syncytiotrophoblast-Derived Exosomes and Their Role in Human Pregnancy - Mincheva-Nilsson, Lucia (Frontiers in Immunology, 2021)
The syncytiotrophoblast (STB) of human placenta constitutively and throughout pregnancy produces and secretes exosomes - nanometer-sized membrane-bound extracellular vesicles from the endosomal compartment that convey cell-cell contact ‘by proxy’ transporting information between donor and recipient cells locally and at a distance. Released in the maternal blood, STB-derived exosomes build an exosomal gradient around the feto-placental unit acting as a shield that protects the fetus from maternal immune attack. They carry signal molecules and ligands that comprise distinct immunosuppressive protein signatures which interfere with maternal immune mechanisms, potentially dangerous for the ongoing pregnancy. We discuss three immunosuppressive signatures carried by STB exosomes and their role in three important immune mechanisms 1) NKG2D receptor–mediated cytotoxicity, 2) apoptosis of activated immune cells and 3) PD-1-mediated immunosuppression and priming of T regulatory cells. A schematic presentation is given on how these immunosuppressive protein signatures, delivered by STB exosomes, modulate the maternal immune system and contribute to the development of maternal-fetal tolerance.